To solve the equation \( 5(x+3) - 7(x-4) = 38 \), follow these steps:
-
Distribute the terms: Apply the distributive property to both terms on the left side of the equation. \[ 5(x) + 5(3) - 7(x) + 7(4) = 38 \] This simplifies to: \[ 5x + 15 - 7x + 28 = 38 \]
-
Combine like terms: Combine the \( x \) terms and the constant terms on the left side. \[ (5x - 7x) + (15 + 28) = 38 \] This simplifies to: \[ -2x + 43 = 38 \]
-
Isolate the variable term: Subtract 43 from both sides of the equation to isolate the term with \( x \). \[ -2x + 43 - 43 = 38 - 43 \] This gives: \[ -2x = -5 \]
-
Solve for \( x \): Divide both sides of the equation by -2 to find the value of \( x \). \[ x = \frac{-5}{-2} \] This simplifies to: \[ x = \frac{5}{2} \quad \text{or} \quad x = 2.5 \]
-
Write the final answer: Conclude with the solution to the equation. \[ x = 2.5 \]
Follow these steps in order to solve the equation successfully!